Pengaruh Kartu Rahasia Terhadap Kemampuan Pemahaman Konsep dan Pemecahan Masalah Siswa Sekolah Dasar Kecamatan Salo - Afriza Rahma Rani; Yolanda Fahrul; Iis Aprinawati (PT Ilmu Data Indonesia, 2024)
This research is motivated by one of the learning objectives, namely maximum student understanding and problem solving abilities. Therefore, to improve students' conceptual understanding and problem solving abilities, it is necessary to develop learning strategies and learning media, one of which is the Inquiry Learning Strategy Using Secret Card Box Media. The aim to be achieved in this research is to determine and analyze the influence of implementing inquiry learning strategies using secret card box media on the ability to understand concepts and solve problems of state elementary school students in Salo District. This type of research is experimental research, quasi experimental design, with Posttest-Only Control Designs. The population in this study were all students in the District Class. Salo, namely 53 people. The sampling technique is to use a saturated sample or census. Based on the Paired Sample T-Test, the results of the research show that the use of the Inquiry Learning Strategy with Secret Card Box Media has an effect on students' concept understanding and problem solving abilities. With the results of this research, teachers, in the learning process, should package learning that is easy to understand, understand and put into practice by students so that students' ability to understand concepts and solve problems can be maximized.